Enzyme replacement therapy in paediatric patients affected by Anderson-Fabry disease leads to improvement in arterial elasticity, but not normalization - Pier Paolo Bassareo; Claudio Barbanti; Andrea Raffaele Marras; Giuseppe Mercuro (Hygeia Press di Corridori Marinella, 2017)
Introduction: Increase in blood pressure, probably due to an impairment in arterial elasticity, is frequent in patients affected by Anderson-Fabry disease (FD). The purpose of this study was to evaluate arterial distensibility in a group of children or adolescent with FD before and after enzyme replacement therapy and compare after enzyme replacement therapy findings with those of healthy controls (C). Material and methods: Sixteen FD patients were recruited (87.5% male; mean age at diagnosis: 13.5 ± 1.5 years; mean age at study: 15.7 ± 2.1 years; mean treatment length: 2.2 ± 0.6 years). Arterial distensibility was evaluated by means of the previously validated non-invasive QKd100-60 method, coupled with a 24-h ambulatory blood pressure monitoring (ABPM). Results: FD subjects before therapy vs after therapy - systolic ABPM: p < 0.05; diastolic ABPM: p < 0.05; mean ABPM: p < 0.05; QKd100-60: p < 0.009. FD subjects after therapy vs C - systolic ABPM: p < 0.01; diastolic ABPM: p < 0.03; mean ABPM: p < 0.02; QKd100-60: p < 0.04. Conclusions: Impaired arterial distensibility in paediatric FD patients implies an early vascular involvement even in these still so young subjects. Enzyme replacement therapy resulted in a significant improvement in arterial elasticity when compared with before treatment findings, but was not able to normalize it. It may explain the differences in ABPM levels.